Preventive Psychoeducation as an Anti-Bullying Strategy for Students at SDN 07 Simpang Utara - Aisyah Nurbaitul Idayah; Naila Faiza Rianti; Annisa Z. S Rahmi (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2026)
This outreach activity was conducted as part of a fieldwork course at SDN 07 Simpang Utara, Pasaman Regency, West Sumatra. The activity aimed to provide an understanding of bullying through psychoeducation. Psychoeducation serves as a preventive measure before the emergence of psychological issues that have negative impacts on individuals or groups. The activity involved 30 students from grades 4 and 5 and was held in January 2026. The method used was psychoeducation, conducted in three sessions: the first session involved presenting material through lectures and discussions; the second was a sharing session; and the third was a story-writing session, where students wrote stories to be posted on a “story tree” to be displayed at the school. This activity resulted in an increased understanding among students regarding the forms, impacts, and ways to avoid bullying, as well as an increase in students’ courage to express their feelings. Psychoeducation can serve as an effective preventive strategy to reduce bullying behavior in elementary school environments.